CARBAMAZEPINE LOADED VESICULAR STRUCTURES FOR ENHANCED BRAIN TARGETING VIA INTRANASAL ROUTE: OPTIMIZATION, IN VITRO EVALUATION, AND IN VIVO STUDY: Carbamazepine intranasal vesicular structures - YASSIN, GHADA E.; AMER, REHAM I.; FAYEZ, AHMED M. (International Journal of Applied Pharmaceutics, 2019)
Objective: Carbamazepine (CBZ) is used as a first line in the treatment of grand mal and partial seizures, but it suffers from many side effects on different systems of the body. The objective of the present study was optimization of CBZ vesicular structures using 23 multifactorial design for the most efficient targeting of CBZ to the brain via the intranasal route. Methods: The concentration of CBZ (10 and 20%), type of vesicles (niosomes and spanlastics) and speed of rotation (200 and 300 rpm) were considered as the independent variables XA, XB and XC respectively, while the dependent variables were particle size PS (Y1), polydispersity index PDI (Y2), zeta potential ZP (Y3) and entrapment efficiency EE (Y4). The study of the effect of different formulation variables was carried out using Design-Expert ® software. CBZ-loaded spanlastics and noisome were prepared by the ethanol injection method and thin film hydration method, respectively. The optimized formulation was subjected to viscosity measurement, in vitro drug release and physical stability studies. In vivo evaluations in rats for the optimized formulation in comparison to oral CBZ suspension was carried out using behavioral assessment by elevated plus maze test, determination of endothelial nitric oxide synthase (e-NOS), reduced glutathione (GSH) and ELISA estimation of TNFα. Results: The selected optimized formulation (F0) containing 20% CBZ and spanlastic vesicular structure showed PS, PDI, ZP, and the EE % of 350.09 nm, 0.830, 16.124mV and 82.777%, respectively. In vitro release study of F0 demonstrated the ability of the F0 to increase drug release in the range time from 10-60 min (p<0.05) when compared with CBZ suspension. The viscosity of F0 was nearly uniform (65 cps). The photomicrograph taken by the transmission electron microscopy (TEM) reveals the spherical shape of F0. Good physical stability for six months of storage at 25˚ C was found for F0. The optimized spanlastic formulation F0 showed a decrease in latency time in behavior assessment test using elevated plus Maze test, a decrease in serum eNOS and TNF-α and increase in GSH when compared with the oral CBZ suspension, in addition to the histopathological study that revealed the more CBZ uptake by the brain. Conclusion: The optimized spanlastic formulation F0 achieved better results when compared with the oral CBZ suspension for targeting the CBZ spanlastics vesicular structure to the brain via the nasal route.